Neuroprotective Effects of Rosmarinus officinalis and Its Pharmacological Potential Against Neurodegenerative Diseases - Fu-Yuan Chen; Wei Yunquan; Qu Jian Lau; Wang Xiang-Li (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2025)
This study investigates the neuroprotective effects of Rosmarinus officinalis (rosemary) in a rodent model of neurodegeneration, focusing on its potential to enhance motor coordination, cognitive function, and reduce oxidative stress and inflammation. The research employs behavioral tests (rotarod, open field, Morris water maze), biochemical analysis (MDA, NO, SOD, CAT), and histological examination to assess the effects of rosemary extract. The results show that rosemary-treated rats exhibit significant improvements in motor coordination and cognitive performance, as well as reduced oxidative stress and inflammation, compared to the vehicle-treated group. Biochemical analysis reveals a marked reduction in MDA and NO levels and an increase in antioxidant enzyme activity (SOD and CAT) in the rosemary-treated rats. Histological examination confirms the preservation of neuronal integrity and a reduction in amyloid-beta plaques and tau tangles, indicating the potential of rosemary to mitigate neurodegenerative pathology. These findings suggest that rosemary extract may provide a natural therapeutic approach for neuroprotection and cognitive enhancement, particularly in conditions like Alzheimer's and Parkinson’s disease. However, further research, including long-term studies and human clinical trials, is necessary to fully explore the efficacy and mechanisms of rosemary in treating neurodegenerative disorders.